A Hubungan Tingkat Literasi Tentang Gizi Dengan Status Gizi Pada Siswi Di SMKN 4 Tanah Grogot Kalimantan Timur - ALMIRA SAVA HANUN (Universitas Airlangga, 2022)
Background: Level of literacy nutrition is the ability to get understand nutritional information in determining daily intake. Nutritional literacy that is owned can affect behavior patterns of adolescents in the choice of daily food. Nutritional problems in adolescents on a national scale in Indonesia still relatively high. At SMKN 4 Tanah Grogot there are 30.9% of students with abnormal nutritional status. Objectives: Study aims to see whether there is a correlation between level of nutrition literacy with nutrition status of students at SMKN 4 Tanah Grogot. Methods: This research is an analytic observational study with case-control method. Population of the study was students at SMKN 4 Tanah Grogot class X and XI totaling 169 students with a total sample of 34 case groups and 34 control groups. The instrument used is questionnaire to measure level of nutrition literacy, namely Health Literacy Measure for Adolescents (HELMA). Nutritional status was measured by the method of body mass index according to age (BMI/U). Chi-square is used to see correlation between the two variables. Resulst: Based on the results, the average level of nutrition literacy of respondents in the low category was in the case group of 20 respondents (58.8%), and in the control group 15 respondents (41.1%). Results of statistical tests showed a negative correlation between level of nutrition literacy and nutrition status (p=0.384). Conclusions: This study shows that there is no significant correlation between the level of nutrition literacy and the nutrition status of students at SMKN 4 Tanah Grogot. So the higher the level of nutritional literacy, it does not have an effect on nutritional status.